2002
DOI: 10.1002/qua.10437
|View full text |Cite
|
Sign up to set email alerts
|

Density functional study of nitroprusside: Mechanism of the photochemical formation and deactivation of the metastable states

Abstract: ABSTRACT:In this article, we present a theoretical investigation about the mechanism of the photochemical formation and deactivation of the metastable states observed in nitroprusside ions. The quantum chemical calculations are based on density functional theory. The peculiar photochemical and photophysical behavior of this molecule has attracted chemists' interest for a while. Due to this interest, many details on the nature of nitroprusside's ground state and its two metastable states were known. However, a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 43 publications
2
23
0
Order By: Relevance
“…This finding is in good agreement with qualitative data from model compounds such as the nitroprusside ion [Fe(CN) 5 (NO)] 3À [25,26] and recent theoretical work on metalloporphyrin NO complexes. [27] The PES was used in molecular dynamics simulations to investigate the relative stability of the three minima.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…This finding is in good agreement with qualitative data from model compounds such as the nitroprusside ion [Fe(CN) 5 (NO)] 3À [25,26] and recent theoretical work on metalloporphyrin NO complexes. [27] The PES was used in molecular dynamics simulations to investigate the relative stability of the three minima.…”
Section: Discussionsupporting
confidence: 88%
“…To facilitate comparison, the energy of the global minimum was set to the same value as in Figure 2. [28,26] and excited states. [29] The behaviour of the energies of the frontier molecular orbitals (HOMOs and LUMOs) in nitroprusside can be expected to be similar to those of the orbitals in ferric nitrosyl heme and were not investigated further here.…”
Section: Environmental Effects On the Fe-no Pesmentioning
confidence: 99%
See 1 more Smart Citation
“…This is consistent with previous studies that have shown that multiple photons are needed to form iso-S 0 from S 0 and that the formation of iso-S 0 relies upon the presence of a stable, photochemically accessible η 2 -S 0 intermediate. 8,21,22 Since neither species B nor C can be assigned to η 2 -S 0 or iso-S 0 , the unassigned peaks must be due to excited state bent-NO complexes. The calculated NO stretching frequencies for both T 1 (1664 cm -1 ) and Since the calculated NO stretching frequencies of S 1 and T 1 are indistinguishable given the accuracy of DFT calculations, 36 we have used the calculated potentials in Figures 10b and 10c to further differentiate between them.…”
Section: Ground and Lowest Excited State Potential Energy Surfacesmentioning
confidence: 99%
“…This is consistent with previous studies that have shown that multiple photons are needed to form iso-S 0 from S 0 and that the formation of iso-S 0 relies upon the presence of a stable, photochemically accessible η 2 -S 0 intermediate. [19,109,110] Since neither species B nor C can be assigned to η 2 -S 0 or iso-S 0 , the unassigned peaks must be due to excited state bent-NO complexes. The calculated NO stretching frequencies for both T 1 (1664 cm −1 ) and S 1 (1659 cm −1 ) agree best with the NO stretching mode of C (1685 cm −1 ).…”
Section: Structures and Harmonic Frequenciesmentioning
confidence: 99%